Impact of the Location of Nasal Septal Deviation on the Nasal Airflow and Air Conditioning Characteristics - Na, Yang; Kwon, Kyung Won; Jang, Yong Ju (Facial Plastic Surgery, 2022)
The location of nasal septal deviation (NSD) directly impacts nasal physiology. The objective is to examine, using computational fluid dynamics (CFD), the difference in the airflow and air conditioning characteristics according to the location of NSD. Twenty patients with septal deviation were divided into two: 10 caudal septal deviation (CSD) and 10 posterior septal deviation (PSD). Physiological variables were compared and numerical models for nasal cavity were created with CT scans. Cases with CSD had distinctive features including restricted airflow partition, larger nasal resistance, and decreased surface heat flux in the more obstructed side (MOS), and lower humidity and air temperature in the lesser obstructed side (LOS). Physiological differences were observed according to the location of septal deviation, CSD cases exhibit significantly more asymmetric airflow characteristics and air conditioning capacity between LOS and MOS.
Keywords: caudal area; posterior deviation; computational fluid dynamics; nasal resistance; air conditioning capacity